The new World Mental Health Report: Believing impossible things. (April 2023) - Allison, Stephen; Bastiampillai, Tarun; Looi, Jeffrey CL; Kisely, Stephen R; Lakra, Vinay
Objective: We examine whether the recent World Health Organization (WHO) report on global mental health uses severity of illness as a criterion in priority setting for resource allocation. Conclusions: The WHO does not prioritise severity in the recent landmark World Mental Health Report. It recommends instead the insuperable task of scaling-up interventions for broadly defined mental health conditions, including milder distress, amongst over a billion people, with the majority living in low- and middle-income countries. Schizophrenia, the most severe and disabling of all psychiatric illnesses, is relatively neglected in the WHO report, and the disability associated with bipolar disorder is underestimated. This is inconsistent with the ethical principle of vertical equity, where the most severe illnesses should receive the greatest priority. The global mental health movement must refocus on deinstitutionalisation, and ensure adequate community and general hospital treatment for severe illnesses, especially the 24 million people with schizophrenia.